Derivational awareness in late bilinguals increases along with proficiency without a clear influence of the suffixes shared with L1. Issue 1 (1st January 2023) - Menut, Amélie; Brysbaert, Marc; Casalis, Séverine
Abstract: Morphological awareness contributes to vocabulary acquisition and reading in bilingual children who learned English after their native language. In line with these considerations, we further investigated L2 processing in late adult bilinguals where questions related to morphology need to be clarified. French–English speakers (N = 92) were assessed for three morphological awareness stages: lexical semantic knowledge, syntactic knowledge, and distributive knowledge. We investigated whether the evolution of morphological awareness was related to L2 proficiency and whether it was facilitated by the presence of suffixes shared in L1 and L2. Our results confirmed the influence of language proficiency at each stage of morphological awareness. However, the hypothesis of an advantage of suffixes shared between French and English was not confirmed as no clear advantage was found for those suffixes. Our findings are discussed in line with the morphological congruence hypothesis and compared with the previous results in the literature.